English Language Teaching in India- A Critical Evaluations of ELT in India - Malini*, S. Devika (International Multidisciplinary Research Journal, 2012)
This paper deals with the contemporary status of English Language Teaching in India. This analysis evaluates the past and the present pattern of English teaching. Unlike the vernacular language teaching, ELT requires more of practical approach as it is being a foreign language. Most of the Indian languages have been learnt and taught only where the particular language is spoken. But, English is in demand beyond the boundaries of states. With having a 74% of Literates in India, there is still only 13% of theme could read and write the English well. When the country is growing in business revolution, pace up with that in the stream of English has become inevitable. Hence, a critical review of ELT in India is not only going to review the pattern but also the suitability of the sorts.